Examining evidence of "shift-contagion" in African stock markets: A CoVaR-copula approach - Gideon Boako; Paul Alagidede (Review of Development Finance, 2017)
This paper examines for the first time contagion to African stock markets with particular attention to the quantification of, and testing for the impact of (extreme) downside movements in foreign exchange and developed stock markets on the (extreme) downside risks in Africa stock markets. Using data of weekly periodicity, the empirical analysis captured the pre, during (both turmoil and acute), and post periods of the 2007-2009 global financial crisis. We analyzed contagion by comparing (extreme) downside cumulative mean distribution conditional value-at-risk (CoVaR) values for African stock markets for successive periods and tested for significance of contagion using the Kolmogorov-Smirnoff (KS) bootstrap technique. We used the KS statistic to test the hypothesis of equality or no systemic impact between the conditional African stock market return quantiles (for different successive sub-samples). CoVaR values are computed from four copula specifications - Gaussian, Student-t, Gumbel and Rotated Gumbel. By situating the empirical analysis within the shift-contagion thesis, we found evidence of contagion from some exchange rate and developed equity markets to African stocks only in the acute and the post-crisis periods. The findings are consistent with the view that global shocks propagation to developing markets may stagger during crisis and intensify post-crisis. A practical implication from the results is that given the relatively scarce resources and levels of technological know-how available to African governments, efforts to wean the continent's equity markets from adverse effects of global market crashes should be geared towards plans and programmes to mitigate the shocks not at the early stages but latter stages, where the effects to Africa could be pronouncedly felt.
Keywords: G10; G15; F30; F31; 650; Shift-contagion; Decoupling; CoVaR-copula; Africa; Exchange rates; Stock markets